The Significance of Modeling the Excavation Sequence in Numerical Analysis of Underground Openings - Y. H. Hatzor; Y. Tal; G. Yagoda-Biran; X. T. Feng (Canadian Institute of Mining, Metallurgy and Petroleum, 2015)
"When studying jointed rock mass deformation around underground openings it is of great importance to model correctly the excavation sequence during the numerical simulation. This is because for effective arching mechanism to develop in the roof minute block displacements must take place and some of the available discontinuities shear strength must be mobilized. If from the beginning of the simulation the underground opening already exists in the numerical model, block displacements into the excavation space will initiate and develop from time zero, before the initial stresses in the model have attained their actual initial level in the field. These initial block displacements are therefore artificial and exist only in the numerical model, not in the physical reality, and may lead to erroneous assessment of the stability of the designed structure, typically on the conservative side. We have introduced sequence excavation capabilities both in the numerical manifold (NMM) and the discontinuous deformation analysis (DDA) methods and show here the advantages of this modification using three different case studies, each illuminating a different aspect of this enhancement.We begin with the 25 meter deep 2000 year old underground Zedekiah limestone quarry below the old city of Jerusalem, Israel, which is still standing today unsupported with a free span of 40 m. We show that when the opening exists from the beginning of the numerical simulation the required friction angle for roof stability is 25 degrees, whereas when the opening is removed after all stresses and displacements in the model have been stabilized the required friction angle for stability is only 15 degrees.We then model the excavation sequence of a tunnel model representing a 2500 meter deep research tunnel in the Jinping hydroelectric project, China, in order to determine the in situ stress field at this depth by a grid search inversion of displacement data obtained using the sliding micrometer technology in the course of tunnel excavation. Thus we are able to constrain the in situ stress field at these depths where standard in situ stress measurement procedures are extremely difficult to execute properly.Finally, we use sequence excavation modeling capability to find the total height of the expected loosening zone around tunnels excavated through columnar jointed basalts which pose a great engineering challenge because of the characteristic dense network of slender prismatic blocks that transect the opening at a steep inclination. We use MPBX data obtained during excavation of a deep tunnel through such a rock mass to validate our numerical results and show that application of standard empirical guidelines for dimensioning rock bolt reinforcement in such rock masses may in fact result in very un-conservative design because existing empirical approaches typically ignore the anisotropic nature of the structure of such rock masses which, as we show, plays a very significant role in determination of the extent, shape, and geometry of the loosening zone around the opening."